The Impact of Instructional Scaffolding on Learner Autonomy: A Literature Review - Chueng, Pich; Heng, Kimkong (Educative: Jurnal Ilmiah Pendidikan, 2025)
Scaffolding is a guided practice in which support is tailored to learners’ current abilities and gradually withdrawn as they gain competence. It plays a vital role in developing learners’ writing skills and autonomy in English as a Foreign Language (EFL) contexts. Drawing on secondary sources, this narrative literature article examines the benefits of instructional scaffolding for enhancing learner autonomy, metacognitive awareness, and writing performance. The review indicates that scaffolding strengthens learners’ self-efficacy, promotes metacognitive awareness, and improves writing quality. Learner autonomy emerges as a key outcome of scaffolding, shaped by learners’ readiness, the timing and type of support, teacher expertise, and contextual factors such as class size and school culture. Scaffolding also enhances metacognitive awareness, empowering learners to take greater responsibility for their learning. In addition, genre-based and process-orientated scaffolding contributes to better writing performance. The article concludes that well-designed scaffolding can help teachers foster learner independence and engagement. Future research should explore culturally responsive scaffolding and its long-term impact on learner autonomy.